2022
DOI: 10.1093/sleep/zsac079.618
|View full text |Cite
|
Sign up to set email alerts
|

0621 Overcoming Obstacles to Recruitment and Community Engagement During COVID-19 and Development of a Digital Community Outreach program

Abstract: Introduction COVID-19 disrupted traditional research infrastructures and processes most notably in-person community recruitment, especially in underrepresented populations like racial ethnic minorities. To find creative and effective strategies, our group implemented and tested the efficacy of a culturally tailored community outreach plan (COP) developed during the US COVID-19 pandemic. Methods In February 2021, we developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Greater exposure to environmental risk factors for poor sleep among racial/ethnic minorities living in disadvantaged neighborhoods Implementing a multilevel approach to reducing ecological factors that disturb sleep, such as inadequate light, noise, allergens and irritants, and air pollution. Suggestions of limitations or suppression of all sources of inadequate light, noise, allergen, irritants, and air pollution during the sleep period in identified communities Determinants of Insufficient Sleep Among Blacks, and Effects on Disparities in Health Outcomes (ESSENTIAL) Study The study aims to ascertain the psychosocial (social network and psychological health) and environmental determinants (social capital, neighborhood, and built environment) of insufficient sleep Mechanisms of Sleep Deficiency and Effects on Brain Injury and Neurocognitive Functions Among Older Blacks (MOSAIC) study The purpose of this study was to assess the determinants of sleep deficiency and delineate their potential role in explaining observed disparities in the brain health of older Black people, indexed by novel Alzheimer disease (AD) brain biomarkers and examinations of cognitive impairment in a multicultural community sample Determinants of Insufficient Sleep in Rural-Urban Settings (DORMIR) study This study provides multilevel evidence supporting epidemiological findings of greater rates of insufficient sleep among Latinos/as that may explain their disproportionate burden of cardiovascular diseases (CVD) risk; the findings can lead to actionable clinical, lifestyle, and policy interventions to improve health 19 Adults 3. A higher rate of short sleep duration increases cardiovascular risk among individuals of African descent and other minorities Adopt a multilevel community-oriented sleep health and promotion education campaign (eg, PEERS-ED, TASHE, and MetSO) Provide incentives to corporate wellness programs that promote sleep and population health among racial/ethnic communities Metabolic Syndrome Outcome Study (MetSO) The MetSO trial has shown that phone-delivered sleep education addressing impediments to OSA (obstructive sleep apnea) care among Blacks was successful in increasing OSA evaluation; the trial demonstrated that tailored OSA education is critical to increasing adherence to recommended OSA care Tailored Approach to Sleep Health Education (TASHE) In the TASHE trial, the authors found that Web-based sleep education significantly increased OSA self-efficacy among Blacks PEERS-ED This randomized controlled trial examined the role of congruent peer sleep educators and social support PEERS-ED in navigating Blacks seeking OSA care 7 4.…”
Section: Solutions To Increase Participation Of Minoritized Communiti...mentioning
confidence: 92%
“…Greater exposure to environmental risk factors for poor sleep among racial/ethnic minorities living in disadvantaged neighborhoods Implementing a multilevel approach to reducing ecological factors that disturb sleep, such as inadequate light, noise, allergens and irritants, and air pollution. Suggestions of limitations or suppression of all sources of inadequate light, noise, allergen, irritants, and air pollution during the sleep period in identified communities Determinants of Insufficient Sleep Among Blacks, and Effects on Disparities in Health Outcomes (ESSENTIAL) Study The study aims to ascertain the psychosocial (social network and psychological health) and environmental determinants (social capital, neighborhood, and built environment) of insufficient sleep Mechanisms of Sleep Deficiency and Effects on Brain Injury and Neurocognitive Functions Among Older Blacks (MOSAIC) study The purpose of this study was to assess the determinants of sleep deficiency and delineate their potential role in explaining observed disparities in the brain health of older Black people, indexed by novel Alzheimer disease (AD) brain biomarkers and examinations of cognitive impairment in a multicultural community sample Determinants of Insufficient Sleep in Rural-Urban Settings (DORMIR) study This study provides multilevel evidence supporting epidemiological findings of greater rates of insufficient sleep among Latinos/as that may explain their disproportionate burden of cardiovascular diseases (CVD) risk; the findings can lead to actionable clinical, lifestyle, and policy interventions to improve health 19 Adults 3. A higher rate of short sleep duration increases cardiovascular risk among individuals of African descent and other minorities Adopt a multilevel community-oriented sleep health and promotion education campaign (eg, PEERS-ED, TASHE, and MetSO) Provide incentives to corporate wellness programs that promote sleep and population health among racial/ethnic communities Metabolic Syndrome Outcome Study (MetSO) The MetSO trial has shown that phone-delivered sleep education addressing impediments to OSA (obstructive sleep apnea) care among Blacks was successful in increasing OSA evaluation; the trial demonstrated that tailored OSA education is critical to increasing adherence to recommended OSA care Tailored Approach to Sleep Health Education (TASHE) In the TASHE trial, the authors found that Web-based sleep education significantly increased OSA self-efficacy among Blacks PEERS-ED This randomized controlled trial examined the role of congruent peer sleep educators and social support PEERS-ED in navigating Blacks seeking OSA care 7 4.…”
Section: Solutions To Increase Participation Of Minoritized Communiti...mentioning
confidence: 92%